2020
DOI: 10.1021/jacs.0c08135
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Ligand-Mediated Regioselective Bonding of Plasmonic Nanoplates and Nanospheres

Abstract: Nanoparticle (NP) clusters are attractive for many applications, but controllable and regioselective assembly of clusters remains challenging. This communication reports a strategy to precisely assemble Ag nanoplates (NP-As) and Au nanospheres (NP-Bs) grafted with copolymer ligands into defined AB x clusters with controlled coordination number (x) and orientation of the NPs. The directional bonding of shaped NPs relies on the stoichiometric reaction of complementary reactive groups on copolymer ligands. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(63 reference statements)
0
30
0
Order By: Relevance
“…Lin et al reported the regioselective self-assembly of Ag nanoplates (A) and Au nanospheres (B) by a polymershielding approach that does not require selective surface blocking (Figure 8a). [86] In this approach, the nanoparticles are first functionalized with a block copolymer composed of a noninteractive block and an interactive block containing acid and base functionalities. Subsequently, the interactive block drives c) Reproduced with permission.…”
Section: Directional Orientation-controlled Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al reported the regioselective self-assembly of Ag nanoplates (A) and Au nanospheres (B) by a polymershielding approach that does not require selective surface blocking (Figure 8a). [86] In this approach, the nanoparticles are first functionalized with a block copolymer composed of a noninteractive block and an interactive block containing acid and base functionalities. Subsequently, the interactive block drives c) Reproduced with permission.…”
Section: Directional Orientation-controlled Self-assemblymentioning
confidence: 99%
“…Subsequently, the interactive block drives c) Reproduced with permission. [86] Copyright 2020, American Chemical Society. d,e) Reproduced with permission.…”
Section: Directional Orientation-controlled Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…But the homopolymer-grafted nanoparticles were not well organized in the block copolymer nanodomains and the improvement in the permittivity was limited. Recently, block copolymer-grafted nanoparticles (BNPs) have emerged as novel assembly building blocks. For example, Leffler et al investigated the self-assembly of BNP thin films prepared from poly­(styrene- b -isoprene) (PS-PI) block copolymers and Cu 2 ZnSnS 4 nanoparticles . They found that the BNPs, unlike the homopolymer-grafted nanoparticles, can self-assemble into highly ordered stripes under the confinement of thin films.…”
Section: Self-assembled Nanostructures Of Ab-g-np/acmentioning
confidence: 99%
“…Nature utilizes an extraordinarily convoluted and delicately balanced interplay of orthogonal covalent and supramolecular interactions to construct highly organized and hierarchical architectures via site-specific interactions by virtue of which the assembly could be achieved at all different scales. , Collagen fibrillation, as one of the most fascinating and inspiring examples, combines the production of proteins via covalent bonding, the folding of protein chain through hydrogen bonding, and the subsequent spontaneous coupling or bundling of these monomeric precursors via site-specific hydrogen bonding and amphiphilic interactions. These hierarchical structures and their intricate assembly process have captured the enthusiasm and imagination of scientists to emulate the intricacy, homogeneity, and versatility of the naturally occurring systems and have represented a central challenge in contemporary materials and chemistry science. Many successful examples have been presented during the past decades toward this ultimate goal of artificial assembly systems, including the hierarchical organization of nanoparticles in a controlled manner, exotic nanostructures from the designed assembly and epitaxial growth of crystalline block copolymers, and directional attachment of patchy colloidal particles to build multidimensional hierarchical suprastructures, and so forth. Although a site-specific design strategy has been applied in these studies and has been demonstrated to be successful in artificial assembly systems, all these achievements have unavoidably adopted multistep approaches.…”
mentioning
confidence: 99%